The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.14202/vetworld.2021.1846-1852
|View full text |Cite
|
Sign up to set email alerts
|

Development of lymphocyte subpopulations in local breed chickens

Abstract: Background and Aim: Local breeds of chicken are known to have relatively higher disease resistance to many endemic diseases and diseases that are highly virulent in commercial chickens. This study aimed to address the lymphocyte subpopulations in three constitutive immune system organs (thymus, bursa of Fabricius, and spleen) in 30, 8-week-old, male local breed chickens. Materials and Methods: The T (CD3+) and B lymphocytes (Bu-1+) were identified through one-color, direct immunofluorescent staining of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The present immunohistochemical results indicated that the (BCs+) were mainly located in both cortex and medulla of the LFs confirming with the findings of [15] in Nandanam chicken and [31]. However, Al-Ogaili and Hameed, [32] reported that around 98% of the lymphocyte population in the BF expressed the Bu-1 marker in chicken, while Sayegh et al [33] and Kozlu et al [34] also reported results for CD79a, CD79b and CD79αcy when examining B-receptor complexes in the BF in chicken and turkey. Our results showed BF provides a microenvironment essential for proper B-lymphocyte maturation.…”
Section: Immunohistochemical Observation Of Bfsupporting
confidence: 91%
“…The present immunohistochemical results indicated that the (BCs+) were mainly located in both cortex and medulla of the LFs confirming with the findings of [15] in Nandanam chicken and [31]. However, Al-Ogaili and Hameed, [32] reported that around 98% of the lymphocyte population in the BF expressed the Bu-1 marker in chicken, while Sayegh et al [33] and Kozlu et al [34] also reported results for CD79a, CD79b and CD79αcy when examining B-receptor complexes in the BF in chicken and turkey. Our results showed BF provides a microenvironment essential for proper B-lymphocyte maturation.…”
Section: Immunohistochemical Observation Of Bfsupporting
confidence: 91%
“…These cells are probably brought in large numbers through the bloodstream from primary immune organs including the thymus to act as local guardians against infectious agents. Indeed, the number of CD3 + T cells was estimated to be 2.5 times higher in the chicken spleen than in the thymus, as shown by flow cytometry (Al‐Ogaili & Hameed, 2021). The total T‐cell population within the cattle egret spleen is expected to be higher than within the chicken spleen as the lymphoid follicles, clustered structures formed mainly by B cells in the chicken spleen (Oláh et al., 2014), are absent in cattle egret spleen.…”
Section: Discussionmentioning
confidence: 96%
“…higher in the chicken spleen than in the thymus, as shown by flow cytometry(Al-Ogaili & Hameed, 2021). The total T-cell population within the cattle egret spleen is expected to be higher than within the chicken spleen as the lymphoid follicles, clustered structures formed mainly by B cells in the chicken spleen(Oláh et al, 2014), are absent in cattle egret spleen.…”
mentioning
confidence: 93%
“…The transcriptomic data of our study fill the gap in the landscape of immune cell development in the bursa of Fabricius of Muscovy ducks. As a central immune organ for B-lymphocytes development unique to birds [ 25 , 26 ], the bursa of Fabricius starts to hatch B-cells at the embryonic stages [ 27 ], but the microenvironment of it that is really beneficial to B-cell maturation is at the neonatal stage [ 28 , 29 , 30 ]. Previous studies have determined that the spleen and bursa of Fabricius are the primary target organs by reovirus [ 17 ], and the consequent immunosuppression usually leads to the deficient B-cells unable to produce an antigen response in young waterfowls [ 31 ].…”
Section: Discussionmentioning
confidence: 99%